2018
DOI: 10.1016/j.jneumeth.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Magnetofection is superior to other chemical transfection methods in a microglial cell line

Abstract: Transfection of BV2 cells using Glial-Mag magnetofection is superior compared to other chemical transfection methods and could be considered as the method of choice to chemically transfect microglial cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Furthermore, Ba/F3 cells used in this study stably express TLR4–MD-2 complex differently tagged (i.e., GFP and Flag), which allowed us to easily study LPS interaction with TLR4 and receptor dimerization, avoiding transfection of primary microglia. In fact, traditional methods of microglia transfection, such as chemical-based methods, viral transduction, and electroporation, exhibit low transfection efficiency, affect cell survival, and promote inflammatory responses [55]. Furthermore, the induction of TLR4 dimerization by LPS was already shown in this cell line [18, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ba/F3 cells used in this study stably express TLR4–MD-2 complex differently tagged (i.e., GFP and Flag), which allowed us to easily study LPS interaction with TLR4 and receptor dimerization, avoiding transfection of primary microglia. In fact, traditional methods of microglia transfection, such as chemical-based methods, viral transduction, and electroporation, exhibit low transfection efficiency, affect cell survival, and promote inflammatory responses [55]. Furthermore, the induction of TLR4 dimerization by LPS was already shown in this cell line [18, 27].…”
Section: Discussionmentioning
confidence: 99%
“…compared the efficiency of magnetofection to other transfection methods using a microglial cell line. They found that Glial-Mag magnetofection of BV2 cells greatly outperformed standard chemical transfection methods; calcium-phosphate precipitation, X-tremeGENE, and Lipofectamine 2000 with an efficiency of 34.95% compared to 0.34, 3.30, and 12.51% respectively (Smolders et al, 2018 ). In contrast to this study, however, Katebi et al found that a static magnetic field reduces the uptake of exogenous oligonucleotide by rooster spermatozoa (Katebi et al, 2016 ).…”
Section: Magnetofectionmentioning
confidence: 99%
“…Magnetoporation is a well‐established magnetically guided delivery combining either chemotherapeutics or nucleic acids (e.g., anionic DNA molecules) with the cationic magnetic nanoparticles (MNPs) (commonly superparamagnetic iron oxide nanoparticles (SPIONs)) via noncovalent bonds. [ 165–167 ] By this means, first cargoes are mixed with MNPs, which are coated and tightly bonded with polyelectrolytes (i.e., polyethyleneimine). Afterward, the field‐induced transport of magnetically labeled complexes takes place through the membrane to concentrate the cargo–MNP complexes in the target cells within a few minutes.…”
Section: Macroengineered Intracellular Deliverymentioning
confidence: 99%
“…Afterward, the field‐induced transport of magnetically labeled complexes takes place through the membrane to concentrate the cargo–MNP complexes in the target cells within a few minutes. [ 167 ] Polymer nanoparticles with iron oxide cores used in this approach are preferable as they enable real‐time noninvasive monitoring of DNA delivery via magnetic resonance imaging (MRI). Accordingly, Kievit and co‐workers illustrated that SPION core coated with a novel copolymer (CP‐PEI) transfection agent is a suitable contrast enhancing agent for MRI to provide earlier detection of lesions and enhanced spatial resolution.…”
Section: Macroengineered Intracellular Deliverymentioning
confidence: 99%